+0  
 
0
30
1
avatar

Calculate \(a^{9} + b^{6} + c^4\div d^3\) assuming that \(a=0, b=1, c=2^3\) and \(d =2\).

 Jan 27, 2019
 #1
avatar+96208 
+1

You literally have this

 

(0)^9  + (1)^6 +  [  (2^3)^4  ÷ (2)^3  ]

 

0 + 1  +   [ 2^12 ÷ 2^3 ]  =

 

1 + 2^9  =

 

513

 

However.... you may have meant

 

[ (0)^9  + (1)^6 +    (2^3)^4 ]  ÷ (2)^3      =

 

[ 1 + 2^12] / 2^3 =

 

[4097 ] / 8

 

 

cool cool cool

 Jan 27, 2019

31 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.